Secretory breast carcinoma in adulthood – A case report with literature review - Ivković Kapicl, Tatjana; Vicko, Ferenc; Popović, Lazar; Djilas, Dragana; Lakić, Tanja (Vojnosanitetski pregled, 2021)
Introduction. Secretory breast carcinoma is rare subtype of breast carcinoma which occurs primarily in children and young adults, so in the past it was called juvenile carcinoma. Case report. A 67-year-old female patient presented with mass of the right breast since one month. After physical, routine laboratory examination and mammography, core needle biopsy was performed and histopathological examination confirmed invasive carcinoma. Immunohistochemically, estrogen-receptors (ER) and progesteron-receptors (PR) showed weak positive reaction in 10% of tumor cells, while human epidermal growth factor receptor-2 (HER-2) was without expression. After an adequate preoperative preparation, operation was done – quadrantectomy with sentinel lymph node biopsy. Postoperatively, the patient was treated with 6 cycles of cyclophosphamide, methotrexate and fluorouracil (CMF) combination, radiotherapy (60 Gy) and tamoxifen. After 5-year follow-up the patient had no signs of the disease. Conclusion. Secretory breast cancer is a rare subtype of invasive breast carcinoma with wide age range of occurrence and good prognosis despite its triple-negative immunophenotype. Although the therapeutic management is non-consensual for this breast cancer special type, surgery is considered the mainstay of the treatment as well as the adjuvant chemotherapy and radiation.
Keywords: breast neoplasms; secretory breast carcinoma; triple neg-ative breast neoplasms; diagnosis; mastectomy, segmen-tal; adult